Random reflections - Lakhama (Lalkhama, 2006)
The book is an amalgamation of random topics which have been beautifully weaved together, and as a result, one gets a full sweep of Mizo history, life, culture, ethos, including political upheavals and their resolution in one go.
Keywords: Random Reflections